2020
DOI: 10.1101/2020.05.26.20111120
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Low-Harm Score for Predicting Mortality in Patients Diagnosed With Covid-19: A Multicentric Validation Study

Abstract: - Importance: Many COVID-19 prognostic factors for disease severity have been identified and many scores have already been proposed to predict death and other outcomes. However, hospitals in developing countries often cannot measure some of the variables that have been reported as useful. - Objective: To assess the sensitivity, specificity, and predictive values of the novel LOW-HARM score (Lymphopenia, Oxygen saturation, White blood cells, Hypertension, Age, Renal injury, and Myocardial injury). - Design: D… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…Several studies have reported risk factors associated with death in patients with COVID-19, although very few propose reliable prediction models, which should be constructed using an adequate sample size and a standardized methodology to avoid significant bias [ 5 , 11 , 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported risk factors associated with death in patients with COVID-19, although very few propose reliable prediction models, which should be constructed using an adequate sample size and a standardized methodology to avoid significant bias [ 5 , 11 , 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three prognostic COVID-19 models have been developed in Mexican patients. The LOW-HARM model [35] is a 100-point scoring system calculated by inputting patient history and laboratory values, in which 65 points was set as the cut-off value to predict death (AUC: 0.80, 95% CI 0.77–0.84), similar to the PH-Covid19 scoring system (AUC: 0.80, 95% CI 0.796–0.804) which advantageously only requires patient history predictors. Another scoring system uses age (cut-off 65 years), comorbidities and pneumonia to predict death [36].…”
Section: Discussionmentioning
confidence: 99%
“…In a UK cohort, during the initial surge of infections, and during oxygen rationing, approximately 62% of patients presented hypoxic, and of those that died 75% (60/80) of patients presented hypoxic (defined broadly in this study as SpO2 <95%)[22]. In a cohort from Mexico, 96% of the patients who died presented with SpO2 under 88%[23].…”
Section: Discussionmentioning
confidence: 99%